ANALISIS WACANA KRITIS TEKS BERITA JAWA POS TERKAIT PENETAPAN DAHLAN ISKAN SEBAGAI TERSANGKA KASUS GARDU INDUK PLN DAN MOBIL LISTRIK (SEBUAH ANALISIS WACANA KRITIS) - Ali Kusno (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
Dahlan Iskan, usually called DI, determined the suspect by the Jakarta High Court in the case of PLN substation and electric cars. DI as an opportunity to direct the owner of Jawa Pos Group in the news related to him. Or it could be without being directed, by itself Jawa Pos down the news that defending DI. This study aims to describe the structure of the text, discourse practice, and ideology news Jawa Pos. This study uses descriptive qualitative critical discourse analysis approach Fairclough models. This research data in the form of documents. Data source document that is news in www.jawapos.com. Based on textual analysis (micro analysis), analysis of discourse practice and socio-cultural dimensions of practice (macro) indicates that Jawa Pos forming diverse ideologies: DI innocent; DI measures taken as a breakthrough over the various problems facing the nation; DI policy conducted entirely in the interests of society; DI own wealth so it is not possible corruption; Errors that occur a former subordinate fault DI; DI being a knight to take over responsibility.